Lifebalance : balancing work with family and personal needs, balancing structure with spontaneity, balancing achievements with relationships - Eyre, Linda (Simon & Schuster New YorkUS, 1997)
Presents the quest for lifebalance as an inner search for 3 kinds of balance, namely: balance of priorities between the needs of our families, jobs and ourselves; balance of attitudes between structure and spontaneity; and balance of goals between achievement and relationships. Describes each kind of balance, and explains how to achieve it. Includes 2 diagnostic balance tests.